Emerging Regulatory Mechanisms Involved in Liver Cancer Stem Cell Properties in Hepatocellular Carcinoma - Lv, Duoduo; Chen, Liyu; Du, Lingyao; Zhou, Lingyun; Tang, Hong (Frontiers in Cell and Developmental Biology, 2021)
Hepatocellular carcinoma (HCC) is the predominant form of primary liver cancer and one of the leading causes of cancer-related deaths worldwide. A growing body of evidence supports the hypothesis that HCC is driven by a population of cells called liver cancer stem cells (LCSCs). LCSCs have been proposed to contribute to malignant HCC progression, including promoting tumor occurrence and growth, mediating tumor metastasis, and treatment resistance, but the regulatory mechanism of LCSCs in HCC remains unclear. Understanding the signaling pathways responsible for LCSC maintenance and survival may provide opportunities to improve patient outcomes. Here, we review the current literature about the origin of LCSCs and the niche composition, describe the current evidence of signaling pathways that mediate LCSC stemness, then highlight several mechanisms that modulate LCSC properties in HCC progression, and finally, summarize the new developments in therapeutic strategies targeting LCSCs markers and regulatory pathways.